Plug-and-Play Control — Definition and Realisation in MATLAB - Bodenburg, Sven; Lunze, Jan (Automatisierungstechnik : AT, 2013)
Technological plants are live systems which are subject to persistent changes. For instance, instrumentations fail or are added, operation modes are changed or communication network topologies are modified. This paper presents a concept to adjust control algorithms to new configurations of the closed loop. The introduced Plug-and-Play Control utilises a communication network to exchange control algorithms between physically separated components. This paper elucidates the concept and describes a realisation of the algorithm exchange by remote procedure calls and model construction functions provided by MATLAB. Experiments on a fluid process illustrate the performance of Plug-and-Play Control and point out the necessary application requirements. Technische Anlagen unterliegen während ihrer Laufzeit ständigen Veränderungen. So fallen z. B. Sensoren aus oder kommen neu hinzu, oder es wird zwischen verschiedenen Arbeitsmodi oder Netzwerktopologien umgeschaltet. In diesem Beitrag wird ein Konzept vorgestellt, um Regelungsalgorithmen an die neuen Systemkonfigurationen anzupassen. Plug-and-Play Control nutzt dabei ein Kommunikationsnetzwerk, um Regelungsalgorithmen zwischen getrennten Komponenten auszutauschen. Der Beitrag erläutert das Konzept und zeigt eine Realisierung der Regelungsalgorithmen mit Hilfe von entfernten Prozeduraufrufen und model construction Funktionen von MATLAB. Abschließend wird über die Erprobung des Konzepts an einem Demonstrationsprozess berichtet.